Investigation and management of abnormal peri-menopausal bleeding. Issue 4 (December 2013) - Turnbull, Hilary; Glover, Alexandra; Morris, Edward P; Duncan, Timothy J; Nieto, Joaquin J; Burbos, Nikolaos
Abnormal peri-menopausal bleeding is a common clinical problem. Decisions to investigate if the menstrual disorders are related to an underlying pathology or represent physiologic changes are often complex especially as no clear guidance is available. The aim of this review is to present a summary of the current available evidence regarding the investigation tools used to evaluate women with abnormal uterine bleeding during menopausal transition and in the post-menopausal period. In this article, we focus mainly on the investigation and exclusion of endometrial carcinoma, as this represents the most common malignancy diagnosed.